47.2k views
5 votes
Which could be the first step and simplifying this expression? Check all that apply.

Which could be the first step and simplifying this expression? Check all that apply-example-1

1 Answer

5 votes


\bf \left( x^3x^(-6) \right)^2\implies \left( x^(3-6) \right)^2\implies \stackrel{1st~Step}{\left( x^(-3) \right)^2}\implies x^(-6)\implies \cfrac{1}{x^6}\\ \qquad \Downarrow\\ \stackrel{\textit{distributing the exponent}}{\left( x^(3\cdot 2)x^(-6\cdot 2) \right)}\\ \qquad \Downarrow\\ \stackrel{1st~Step}{x^6x^(-12)}\\ \qquad \Downarrow\\ x^(6-12)\\ \qquad \Downarrow\\ x^(-6)\\ \qquad \Downarrow\\ \cfrac{1}{x^6}

User JeremyKirkham
by
4.9k points